FINANCIAL STATEMENT FRAUD DETECTION ANALYSIS IN FRAUD TRIANGLE PERSPECTIVE (Empirical Study in Manufacturing Companies in The Consumer Goods Industry Sub-Sector on the Indonesia Stock Exchange in 2018-2020) - Siti Muariya; Tutik Dwi Karyanti; Maria Theresia Heni Widyarti (Jurnal Aktual Akuntansi Keuangan Bisnis Terapan (AKUNBISNIS), 2022)
This study aims to determine the effect of financial targets, financial stability, external pressure, ineffective monitoring, and rationalization on fraudulent financial statements. The population in this study are the consumer goods industry sub-sector of the manufacturing companies sector listed on the Indonesia Stock Exchange for the 2018-2020 period. Samples were selected using a purposive sampling method. The analysis method of this research uses multiple linear regression. The results of this study indicate that financial stability and rationalization have a significant effect on fraudulent financial statements, while financial targets, financial stability, external pressure, ineffective monitoring, and rationalization simultaneously affect fraudulent financial statements with a contribution value of 21.4% the rest is influenced by other variables.